Establishing the feasibility of a community and primary health care intervention to raise awareness of symptoms of Type 1 Diabetes—The Early Detection of Type 1 Diabetes in Youth (EDDY) study. Issue 8 (6th March 2017) - Townson, J; Gregory, J W; Cowley, L; Gallagher, D; Channon, S; Robling, M; Williams, D; Hughes, C; Murphy, S; Lowes, L
Abstract : Aims: To design, develop, and evaluate the feasibility of delivering a multi‐component community based intervention to parents and primary health care professionals to raise awareness of the symptoms of Type 1 diabetes (T1D) in childhood in 3 adjoining borough counties of South Wales. Materials and Methods: Parent and primary health care advisory groups were established to design the intervention. Qualitative interviews with stakeholders and parents assessed the acceptability, feasibility and any potential impact of the intervention. Results: The parent component of the intervention developed was a re‐useable shopping bag with the 4 main symptoms of T1D illustrated on the side, based on the road traffic system of red warning triangles and an octagon "stop" sign stating "Seek Medical Help". Accompanying the bag was an A5 leaflet giving further information. Both were overwrapped with clear plastic and delivered to 98% (323/329) schools, equating to 101 371 children. The primary health care professional component was a dual glucose/ketone meter, single use lancets, stickers, the A5 parent leaflet displayed as a poster and an educational visit from a Community Diabetes Liaison Nurse. 87% (73/84) of GP practices received the intervention, 100% received the materials. The intervention was delivered within Cardiff, the Vale of Glamorgan and Bridgend. Qualitative analyses suggest that the intervention raised awareness and had some impact. Conclusion: This study showed that it is feasible and acceptable to design, develop and deliver a community based intervention to raise awareness of T1D. There is some suggestion of impact but a definitive evaluation of effectiveness is still required.